Analiza fondurilor europene în proiecte PC7 prin participarea României - Margareta FLORESCU (Revista Transilvană de Ştiinţe Administrative, 2010)
The research potential is a matter closely related to the resources of an organization. Thus, it is necessary to define these resources and to highlight those which play an important role in reference to research potential. The evaluation of the research potential and the design of actions meant to enhance it in order to successfully participate in FP7 programs, represent strategic activities for every type of organization operating in the field of research. Therefore, participation in FP7 programs does not represent an end in itself but rather an important stage in accomplishing the most important strategic component – namely the accomplishment of the sustainable competitive advantage (SCA); all the other components of the strategy are subordinated to this. The achievement of the system for determining the research potential is built on the transfer of know-how from various fields of the management – general management, strategic management, management of quality.